Sementes de Futuro: Memória, Cultura e Resistência no MST - Gonçalves, Adelaide (Trabalhos de Antropologia e Etnologia, 2020)
Around the memories of the Ligas Camponesas, in Northeast of Brazil, in the mid-twentieth century, we approach the meanings of the past and present struggles against landlordism violence and the state, as well as defense of popular land reform. In MST’s formation we observed its territorialization through the Occupation struggle, managing the Camp and when each settlement conquered affirm the MST as a socio-territorial movement. Examining the situation of the 1980s, noting the MST’s roots, the socio-religious culture of Christianity Liberation and following the systematic production of the MST, in their collective of Education, Arts and Culture, we highlight, reflection on the Mystic, Marches and the Land’s Pedagogy as an important experience, as a visceral human experience. We bring out the contents of social memory activating the commitment of struggle in the present time and expressing the values in the rites, symbols and records of convocation and evocation.